(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
When the Yoruba world and mythopoesis (or mythopoeia) are considered in the arena of literature, one writer that readily comes to mind is Wole Soyinka. Several aspects of the Yoruba society have received various forms of exposures through his penmanship. His Death and the King’s Horseman counts among the lot. As would be expected, this piece of drama has received a lot of interpretations as a literary archetype of African nay Yoruba tragedy, mythology, rituals, tradition and custom, et cetera. Even the playwright’s stance against reading the work as a treatise on culture conflicts has been neglected by critics, who simply insist on exercising their reader-response authority in viewing the text as a masterpiece on the clash between tradition and modernity as well as between the West and African cultures. But then, this present work is tailored towards exploring the motifs of duty and death in the text in the light of Kant’s Deontology. Even though some scholars have attempted to delineate on the themes of duty and death as unique themes in the text, none has been seen to take on the nexus between the two, particularly through the prism of Kant’s deontological theory. This is exactly what this work sets out to do through the method of textual analysis with a view to deciphering to what extent the motifs of duty and death either adhere to or contravene the Categorical Imperative of Kant’s Duty Ethics. The goal is to seek any moral justification for the ritual duty of death that controls the entire dramaturgy and controversies of the play. In the end, it finds that while this pivotal ritual duty of death is partially justified in some respects, it is largely condemnable in many other respects in accordance with the theoretical framework of Kant’s Deontology.